INO80 exchanges H2A.Z for H2A by translocating on DNA proximal to histone dimers - Sandipan Brahma (Nature Portfolio, 2017)
Chromatin remodellers usually mobilize or disassemble nucleosomes by translocating along the nucleosomal DNA at the H3-H4 interface. Here, the authors provide evidence chromatin remodeller INO80 translocates along DNA at the H2A-H2B interface and displaces DNA from the surface of H2A-H2B.